HUBUNGAN KOORDINASI MATA TANGAN DAN KELENTUKAN PERGELANGAN TANGAN DENGAN KEMAMPUAN PUKULAN FOREHAND DALAM PERMAINAN TENIS MEJA ATLET PUTRA PTMPI KECAMATAN TUALANG-PERAWANG - Imanuel Siagian; Saripin Saripin; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the observations that have been done on the athletes sonsPTMPI Tualang- Perawang district found some of problems that is not good athlete indoing series of forehand punch movement so that cause movement not maximal indirecting ball right at target, then when the ball blows down in the area that is easilyaccessible by the opponent, even the athlete’s wrists stiffen so that the perfection of theball with the blade is not right so that the direction of the ball fall out of the opponenttable and not over the net. The cause of this allegedly because of lack of goodcoordination the hand and flexibility the wrist the player so the effect on when the shots.As in the basic techniques a tennis table game what to get a move that effectively andefficiently this need is based on the control of a good technique, the basic techniqueswith table tennis like technique holds the bet, service, technical leg movements, and theblow. The abjective in this study is to find out if there is the relationship between thehand and flexibility the wrist with a forehand in the game of table tennis athletes sonsPTMPI the Tualang-Perawang. The population in this study is the athete’s son PTMPIthe Tualang-Perawang as many as 6 people. The sampling of the whole population (thetotal sampling). Instrument for this research is a test of throwing captured a tennis ball,it ains to measure the movement of the coordination of the eyes and hands. Then the testfleksi, the aim is to find out hw much flexibility the wrist of a degree that is used. Then abackboard, the aim is to determine the ability a forhan on the athlete’s. Thereafter, thedata were sampled with statistics, to test the normality by the lilifors test at a significantlevel of a0.05. Based on the results of research, it can be concluded as follows. Fromthe results by the eye coordination and flexibility the wrist had a relationship with aforehand in the game of table tennis athletes sons PTMPI the Tualang-Perawang,where rhitung on significant level α (0.05) = 0.811 it means that rhitung (0.913)> rtab(0.811)Keywords : Eye coordination, wrist flexibility, forehand blow.